Carbohydrate structure–activity relations of Au-catalysed base-free oxidations: gold displaying a platinum lustre. Issue 15 (22nd March 2022) - van der Klis, Frits; Gootjes, Linda; Verstijnen, Noud Hendrik; van Haveren, Jacco; Stephan van Es, Daniël; Bitter, Johannes Hendrik
Abstract : Gold mimicking Platinum in base-free catalytic carbohydrate oxidations. Abstract : This paper describes the base-free gold-catalysed oxidation of four different carbohydrates in a packed bed plug flow reactor. The influence of the carbohydrate structure on the catalytic activity and selectivity was investigated by comparing two neutral sugars (glucose (Glc) and galactose (Gal), both with primary alcohols at C6), with their sugar-acid analogues (glucuronic acid (GlcA) and galacturonic acid (GalA), both with carboxylic acids at C6). The orientation of OH-groups at the C4-position ( equatorial in Glc/GlcA and axial in Glc/GlcA), and the C6-functionality (primary alcohols in Gal/Glc and carboxylic acids in GalA/GlcA) has a profound influence on the catalytic activity. When the OH-groups are in an axial position their reactivity was higher compared to the OH-groups in the equatorial position for both the sugars and the sugar acids. In addition the reactivity of carbohydrates over Au-catalysts under base-free conditions is different compared to alkaline conditions, and is more in line with a Pt-catalysed dehydrogenation mechanism.